The evolution of huge Y chromosomes in Coccinia grandis and its sister, Coccinia schimperi - Janousek, Bohuslav; Gogela, Roman; Bacovsky, Vaclav; Renner, Susanne S (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2022)
Microscopically dimorphic sex chromosomes in plants are rare, reducing our ability to study them. One difficulty has been the paucity of cultivatable species pairs for cytogenetic, genomic and experimental work. Here, we study the newly recognized sisters Coccinia grandis and Coccinia schimperi, both with large Y chromosomes as we here show for Co. schimperi. We built genetic maps for male and female Co. grandis using a full-sibling family, inferred gene sex-linkage, and, with Co. schimperi transcriptome data, tested whether X- and Y-alleles group by species or by sex. Most sex-linked genes for which we could include outgroups grouped the X- and Y-alleles by species, but some 10% instead grouped the two species' X-alleles. There was no relationship between XY synonymous-site divergences in these genes and gene position on the non-recombining part of the X, suggesting recombination arrest shortly before or after species divergence, here dated to about 3.6 Ma. Coccinia grandis and Co. schimperi are the species pair with the most heteromorphic sex chromosomes in vascular plants (the condition in their sister remains unknown), and future work could use them to study mechanisms of Y chromosome enlargement and parallel degeneration, or to test Haldane's rule about lower hybrid fitness in the heterogametic sex. This article is part of the theme issue 'Sex determination and sex chromosome evolution in land plants'.
Keywords: XY divergence; genetic map; heteromorphic XY chromosomes; cytogenetics; sex chromosomes; Evolution, Molecular; molekulární evoluce; Cucurbitaceae; chromozomy rostlin; Chromosomes, Plant